Shakespeare and ecocritical theory - Egan, Gabriel (London : Bloomsbury Arden Shakespeare, 2015)
'Combining the latest scientific and philosophical understanding of humankind's place in the world with interpretative methods derived from other politically inflected literary criticism, ecocriticism is providing new insights into literary works both ancient and modern. With case-study analyses of the Tragedies, the Comedies, the History Plays and the late Romances as well as the Sonnets, this book is a wide-ranging introduction to reading Shakespeare in light of contemporary ecocritical theory. Shakespeare and Ecocritical Theory also features a glossary of key critical terms and guides to further reading and online resources, making this an essential resource for students and scholars of Shakespeare at all levels'--
Machine generated contents note: -- Introduction -- 1. The Rise of Ecocriticism -- 2. Shakespeare and the Meaning of'Life' in the 21st Century -- 3. Animals in Shakespearean Ecocriticism -- 4. Shakespearean Ecocritisism Across the Genres -- 5. Crowds and Social Networks in Shakespeare -- Conclusion.
Includes bibliographical references and index.
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- Natural history; Ecocriticism